Estudio de factibilidad para la creación de una Cooperativa de Ahorro y Crédito en la Parroquia El Lucero, Cantón Calvas, Provincia de Loja - Vargas Abad, Johana Katheryne (2016)
This study aims to determine the feasibility of creating a credit union in the parish Lucero has been developed in accordance with the general objectives put forward as. Conduct a market study that allows me to meet supply and demand, implement a technical study that allows me to project engineering, in addition to its size, location and functioning, develop a legal administrative study for the creation of the Cooperative Savings and Credit, develop the financial evaluation of the business plan for the creation of the credit union, so carefully applied methods and techniques described in this paper, with the following results, in each of the study to this effect were required to apply. The market study, it was determined that there is an unmet demand for the first year of 756 applicants and for the fifth year of 668 applicants this because there is a population decline of -0.82% since the people migrate to other but they return next vacation time to their homeland, regarding the Technical Study, served to detail the exact location where the cooperative will work, the size of its facilities and both human, material and financial resources required for the implementation of the project. 6 It was also determined in the administrative and legal study, the legal basis for the creation of legal personality and regulatory bodies to which the Cooperative is governed as is the Law of Popular and Solidarity Economy and its regulations; as well as its functional and organizational structure, whereby its statutes and hierarchical order of their officers was determined. In the Economic Survey, the initial investment for the implementation of the project is $ 73,244.32, which will be invested in fixed assets and working capital deferred determined. Funding sources for both the initial investment and lending to be with contributions from 100 members of $ 70,000.00 by. Another source of financing will be the average income savings and deposit taking by certificates of contribution considering that there saving capacity as demonstrated in the market study. The financial evaluation, the results achieved are acceptable as compared to the initial investment would cover within 5 years of life since the NPV is $ 42.760,91; The internal rate of return is 29,15%; investment recovery period is 3 years, 3 months and 2 days, cost benefit ratio is 1.39. 7 In the sensitivity analysis it was determined that the project is not sensitive to increased costs on a 5.394% and is not sensitive to a decrease in its revenue 3,8612% and can be set according to your results. Finally it can be concluded that this project at the end of five years will be sensitive in both their costs and revenues which the implementation of a savings bank would be more feasible but should not ignore the creation of the cooperative and if generate utilities but not exceeding percentages thrown.